(Dis)legitimacy of consciences in stalinist Russia - de Paula, Luciane [UNESP]; de Santana, Wilder Kleber Fernandes; Francelino, Pedro Farias; da Silveira, Éderson Luís (Universidade Estadual de Maringa, 2021)
This paper aims to analyze the process of (dis)legitimacy of artistic-sociological consciences in Russia during the early years of Stalinist rule, in order to recover the history of language studies and the context of production of Bakhtinian writings. The method that underlies the reflection undertaken is based on the theoretical-methodological assumptions of Bakhtin (2006 [1979]; 2010 [1920-24]), Medviédev (2016 [1928]) and Volóchinov (2017 [1929], 2013), among others, which present criticisms of the formalist model, prevailing in Stalinist Russia. Historical sources are also used (Deutscher, 2006; Fitzpatrick, 2017) to investigate the political-ideological context of the post-revolution of 1917. The relevance of this manuscript is realized in the contribution of a contemporary but not anachronistic look, which brings to light a critical reading about the construction of philosophical and ethical (aesthetic) approaches on artistic-sociological consciences in Russia. The results show that, despite the execrable situation to which the members of the Bakhtin Circle were subjected amid attempts to (un)artistic legitimacy by the Russian state, researchers and intellectuals resisted and proposed to (re)think the aesthetic object (literary) as conceived by Stalin, whose primary proposal was the unification of the Russian language. Thus, this is not only language movements for the implementation of a linguistic system conception, but also a sociohistorical-cultural reality.
(Des)legitimidade de consciências na Rússia stalinista
Keywords: Art; Bakhtin; Language; Medviédev; Sociology; Volóchinov